Impact of a Best Practice Prevention Bundle on Central Line-associated Bloodstream Infection (CLABSI) Rates and Outcomes in Pediatric Hematology, Oncology, and Hematopoietic Cell Transplantation Patients in Inpatient and Ambulatory Settings. Issue 1 (January 2021) - Ardura, Monica I.; Bibart, Mindy J.; Mayer, Lauren C.; Guinipero, Terri; Stanek, Joseph; Olshefski, Randal S.; Auletta, Jeffery J.
Abstract : Background: Pediatric hematology, oncology, and hematopoietic cell transplantation (HCT) patients are at increased risk for bloodstream infections. The authors sought to evaluate the influence of a standardized best practice central venous catheter (CVC) maintenance bundle on the burden of and risk factors for mucosal barrier injury (MBI) and non-MBI central line-associated bloodstream infections (CLABSIs) across a common inpatient and ambulatory continuum in this high-risk population. Methods: A retrospective cohort study of patients with underlying malignancy, hematologic disorders, and HCT recipients with a CVC in place at the time of CLABSI diagnosis in both inpatient and ambulatory settings from January 1, 2012 to December 31, 2016. Descriptive, nonparametric statistics were used to describe patient characteristics and outcomes. Logistic regression analyses were applied to identify potential risk factors for inpatient versus ambulatory and MBI versus non-MBI CLABSI. Results: During the 5-year period, 118 of 808 (14.6%) patients had 159 laboratory-confirmed CLABSIs for ambulatory and inpatient CLABSI rates of 0.27 CLABSI/1000 and 2.2 CLABSI/1000 CVC days, respectively. CLABSI occurred more frequently in hospitalized patients after HCT and with underlying leukemia, most frequently caused by Gram-negative bacteria. MBI CLABSI accounted for 42% of all CLABSI with a 3-fold higher risk in hospitalized patients. Having multiple CVC or a CVC that was not a port independently associated with higher CLABSI risk. Conclusions: In our cohort, non-MBI CLABSI continued to account for the majority of CLABSI. CVC type is independently associated with higher overall CLABSI risk. Further studies are needed to reliably define additional prevention strategies when CLABSI maintenance bundles elements are optimized in this high-risk population. Abstract : Supplemental Digital Content is available in the text.